The effect of product quality and store atmosphere on customer satisfaction at cirebon coffee chop - Aziz, Muhammad Abdul; Agnain, Muhammad; Hermawan, Fery; Hernidatiatin, Lis Tatin (Jurnal Mantik, 2025)
This study aims to analyze the influence of product quality and store atmosphere on customer satisfaction at G.O Coffee Shop in Cirebon. The quality of the products in this study includes eight dimensions, including performance, features, reliability, specification suitability, durability, ease of repair, aesthetics, and quality perception. Meanwhile, store atmosphere is measured through four dimensions, namely exterior, general interior, store layout, and interior display. Customer satisfaction is measured based on the suitability of expectations, interest in returning visits, and willingness to recommend. The research uses a quantitative approach with a correlational descriptive method. A sample of 168 respondents was obtained through purposive sampling techniques and analyzed using multiple linear regression. The results of the study show that both product quality and store atmosphere have a positive and significant effect on customer satisfaction, with product quality having a more dominant influence. These findings support the importance of integrated management between product quality and store atmosphere in shaping a satisfactory customer experience. A strategy that emphasizes the synergy of the two elements is expected to increase customer loyalty and recommendations in the long run